Obstacles to Supporting Small Projects in Duhok Governorate : : An Exploratory Study of the Opinions of a Sample of Investors in Duhok Governorate - Shaaban, Farsat A. (Mitanni Journal of Humanitarian Sciences, 2023)
The main aim of this study to identify the real obstacles that prevent investors to support the study projects of graduates in Duhok Governorate. The problem of the study was the existence of unemployment among graduate students and the lack of support from the government and investors for their projects. The study is based on a hypothesis that assumes the existence of obstacles, realistic, and linking investors to the support of graduate students and their small projects. The theoretical side of the study is based on the relevant literature, the study rely on the method of interviewing and asking precise questions to complete the practical side. (35) Investors were interviewed. The investors' answers were analyzed, and the study reached a set of conclusions, the most important of which are: There are three main reasons that prevent investors from supporting small projects, the most one : which is the students have not experience to manage their projects